Effects of Clinacanthus nutans Extracts on Cytokine Secretion in PMA-Induced U937 Macrophage Cells - Swee Hong Ooi; Nur Mazidah Noor Mohamed; Ravi Kumar Kalaichelvam; Vuanghao Lim; Ida Ismail* (Iranian Society of Pharmacognosy, 2021)
Background and objectives: Clinacanthus nutans (Burm f.) Lindau (C. nutans) is a well-known traditional medicine in South East Asia and consists of abundant phytomedicinals properties. This study aimed to investigate the effects of C. nutans ethanol and aqueous extracts on interleukin-4 (IL-4) and interleukin-13 (IL-13) cytokines secretion in phorbol 12-myristate 13-acetate phorbol-12-myristate-13-acetate (PMA)-induced U937 macrophages. Methods: Sequential ultrasonic-assisted extraction was carried out using ethanol (ETOH) and water, by applying 1:10 ratio of leaves powder to the solvent volume. U937 cells were incubated with 25 nM PMA for 72 h to induce macrophage differentiation. The macrophage differentiation was assessed based on the cell morphological changes, cell viability and, CD14 and CD11b expression by using flow cytometry. The macrophages were incubated with both ETOH and aqueous extracts at 0.25, 0.5, 1.0, 2.0, 4.0 and 8.0 mg/mL concentration for 48 h. The viability of the extract-treated cells was assessed using PrestoBlue cell viability assay and the IL-4 and IL-13 secretions were assessed by using Enzyme-Linked Immunosorbent Assay (ELISA). Results: PMA stimulation caused morphological changes of U937 cells from round-shaped, non-adherent to larger irregular-shaped, adherent cells, and a reduction of cells viability to 87%. CD14 expression was down-regulated from 7% to 4.5% upon PMA stimulation. CD11b expression was up-regulated from 16% in untreated cells to 38% in PMA-treated cells. ELISA results showed that 1 mg/mL of ETOH and AQ extracts stimulated 1200 and 1800 pg/mL IL-4 secretions, respectively. However, both extracts caused minimal IL-13 secretion.  Conclusion: Clinacanthus nutans aqueous extracts stimulated IL-4 production higher than ETOH extract in PMA-induced U937 macrophages.